Assessment of Natural Radioactivity in Drinking Water from some Selected Districts of Michika, Adamawa State, Nigeria (Gadau Journal of Pure and Allied Sciences, 2024)
Radionuclides are source of radiation that were recorded to have damaging health effects for people living in a community with high back-ground radiation. This study was carryout to assess natural radioactivity in drinking water sources at some districts of Michika, Adamawa State, Nigeria. Twenty-four (24) water Samples from three different sources (surface, borehole and well), were collected and analyzed using a thallium activated 3ʺ x 3ʺ sodium iodide [NaI (TI)] detector connected to ORTEC 456 amplifier available at Center of Energy Research and Training (CERT), Zaria. The results show that the mean activity concentration for 226Ra, 232Th and 40K are 57.05, 40.31 and 193.6 Bql-1 for borehole samples, 82.09, 23.0 and 199.4 for surface samples and 87.65, 38.82 and 215.7 for well samples. These values are higher than the control value of activity concentration set by UNSCEAR 200). The mean absorbed dose rate (D) for borehole, surface and well water samples were found to be 58.78, 60.1 and 72.94 nGy/h respectively. The mean values surface and well samples were higher than the maximum accepted value of 59nGy/h as recommended by (UNSCEAR, 2000) however, borehole is within the MCL. The mean values of total annual effective dose for borehole, surface and well water samples were 0.08, 0.08 and 0.09 respectively. These values are below 0.12, 0.1 and 1.0 mSvy-1 as recommended by UNSCEAR, WHO and ICRP. Also, the mean values of Radium Equivalent Activity were 129.6, 130.4 and 159.8 Bql-1 for borehole, surface and well water samples respectively. All the value of Raeq were below the maximum recommended value of 370 Bql-1. The mean value of total cancer risk is 3.18E-06, 3.25E-06 and 3.91E-06 for borehole, surface and well water samples respectively. All the mean values were above the acceptable range of 1E-06 to 1E-04. Based on our findings, the water sources in this area are not safe for domestic use. However continuous radiological monitoring of the water is recommended to safeguard the health of the populace.